Basidiomycetes Are Particularly Sensitive to Bacterial Volatile Compounds: Mechanistic Insight Into the Case Study of Pseudomonas protegens Volatilome Against Heterobasidion abietinum - Prigigallo, Maria Isabella; De Stradis, Angelo; Anand, Abhishek; Mannerucci, Francesco; L’Haridon, Floriane; Weisskopf, Laure; Bubici, Giovanni (Frontiers in Microbiology, 2021)
Volatile organic compounds (VOCs) play an important role in the communication among organisms, including plants, beneficial or pathogenic microbes, and pests. In vitro, we observed that the growth of seven out of eight Basidiomycete species tested was inhibited by the VOCs of the biocontrol agent Pseudomonas protegens strain CHA0. In the Ascomycota phylum, only some species were sensitive (e.g. Sclerotinia sclerotiorum, Botrytis cinerea, etc.) but others were resistant (e.g. Fusarium oxysporum f. sp. cubense, Verticillium dahliae, etc.). We further discovered that CHA0 as well as other ten beneficial or phytopathogenic bacterial strains were all able to inhibit Heterobasidion abietinum, which was used in this research as a model species. Moreover, such an inhibition occurred only when bacteria grew on media containing digested proteins like peptone or tryptone (e.g. Luria-Bertani agar or LBA). Also, the inhibition co-occurred with a pH increase of the agar medium where the fungus grew. Therefore, biogenic ammonia originating from protein degradation by bacteria was hypothesized to play a major role in the fungus inhibition. Indeed, when tested as a synthetic compound, it was highly toxic to H. abietinum (lethal dose 50% or LD50 = 1.18 M; minimum inhibitory quantity or MIQ = 2.14 M). Using gas chromatography coupled to mass spectrometry (GC/MS), eight VOCs were found specifically emitted by CHA0 grown on LBA compared to the bacterium grown on potato dextrose agar (PDA). Among them, two compounds were even more toxic than ammonia against H. abietinum: dimethyl trisulfide had LD50 = 0.02 M and MIQ = 0.2 M, and 2-ethylhexanol had LD50 = 0.33 M and MIQ = 0.77 M. The fungus growth inhibition was the result of severe cellular and sub-cellular alterations of hyphae occurring as early as 15 minutes of exposure to VOCs, as evidenced by transmission and scanning electron microscopy observations. Transcriptome reprogramming of H. abietinum induced by CHA0’s VOCs pointed out that detrimental effects occurred on ribosomes and protein synthesis while the cells tried to react by activating defense mechanisms, which required a lot of energy diverted from the growth and development (fitness cost).